2016
DOI: 10.4102/ojvr.v83i1.958
|View full text |Cite
|
Sign up to set email alerts
|

Contagious bovine pleuropneumonia: Seroprevalence and risk factors in Western Oromia, Ethiopia

Abstract: Contagious bovine pleuropneumonia (CBPP) is one of the most important threats to cattle health and production in Ethiopia. At the livestock farm of the Bako Agricultural Research Center, an outbreak of respiratory disease of cattle occurred in May 2011, and many animals were affected and died before the disease was diagnosed. Therefore, this study was designed to determine the seroprevalence of CBPP antibodies in selected districts of Western Oromia Region and to assess the potential risk factors for the occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
9
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 9 publications
6
9
4
Order By: Relevance
“…This finding is consistent with the study of Atnafie et al (2015) who reported a significant association of body condition score with the CBPP seropositivity in abattoirs at Bishoftu and export oriented feedlots around Adama in which a high seroprevalence was recorded in animals with poor body condition (18%) than in medium (12.5%) and good body condition score (6.4%), which was significantly associated with the occurrence of the disease (p<0.05). Nevertheless, our finding do not agree with the work of Daniel et al (2016) who reported no significant association of body condition score with CBPP sero-positivity.…”
Section: Sero-epidemiology and Putative Risk Factors Exposing To Contcontrasting
confidence: 99%
See 4 more Smart Citations
“…This finding is consistent with the study of Atnafie et al (2015) who reported a significant association of body condition score with the CBPP seropositivity in abattoirs at Bishoftu and export oriented feedlots around Adama in which a high seroprevalence was recorded in animals with poor body condition (18%) than in medium (12.5%) and good body condition score (6.4%), which was significantly associated with the occurrence of the disease (p<0.05). Nevertheless, our finding do not agree with the work of Daniel et al (2016) who reported no significant association of body condition score with CBPP sero-positivity.…”
Section: Sero-epidemiology and Putative Risk Factors Exposing To Contcontrasting
confidence: 99%
“…The difference was also positively associated with CBPP sero-positivity (p<0.05). This finding coincided with that of Daniel et al (2016) who reported a higher sero-positivity of CBPP in cross (37.2%) than in local breeds (27.4%) but their finding revealed a negative association of breed with sero-positivity of the disease(p>0.05).…”
Section: Sero-epidemiology and Putative Risk Factors Exposing To Contsupporting
confidence: 88%
See 3 more Smart Citations